Characteristics of "Kolang-kaling" (Sugar Palm Fruit Jam) with Added Natural Colorants - Sayuti, Kesuma; Yenrina, Rina; Anggraini, Tuty (Pakistan Journal of Nutrition, 2017)
Background: Sugar palm fruit contains galactomannan which has the potential to be used as raw material for making jam. In this study, natural colorants from Asian melastome fruit, Java plum fruit rind and Mangosteen fruit rind were added to sugar palm fruit pulp for making jam. Materials and Methods: This study used an experimental design with 3 natural colorants where each colorant had 4 treatments of 6, 8, 10 or 12%. Results: The addition of different natural colorants had a significant effect on the characteristics of sugar palm fruit jam. Chemical analysis of the jam with the addition of Asian melastome fruit juice, Java plum rind and Mangosteen fruit rind was as follows: Moisture content (21.81-30.56, 31.82-38.43 and 15.30-26.18%), water activity (0.59-0.67, 0.62-0.80 and 0.63-0.73), total dissolved solids (50.00-67.50, 57.5-62.33 and 63.33-72.17%), ash content (0.02-0.11, 0.23-1.57, 0.075-0.087%), pH value (3.43-3.45, 3.12-3.61 and 3.31-3.35), total sugar (18.03-35.67, 22.40-50.36 and 47.75-53.23%), dietary fiber (7.10-8.89, 7.37-8.38 and 3.80-8.34%) and crude fiber (4.05-4.41, 1.53-2.85 and 1.24-2.66%). Conclusion: The addition of Asian melastome fruit juice, Java plum rind and Mangosteen fruit rind had a significant effect on the characteristics of sugar palm fruit jam. All of the jams made from natural colorants were considered acceptable by panelists.